The Effectiveness of Acceptance and Commitment Therapy on Psychological Well-being, Resilience, and Hope for Life in Coronary Heart Disease Patients with High Blood Pressure Visiting Shahid Rajaei Hospital - Naseri, Atena; Rahmanian, Mahdieh; Rafieipour, Amin (Health Nexus, 2024)
The purpose of this study was to examine the effectiveness of Acceptance and Commitment Therapy (ACT) on psychological well-being, resilience, and hope for life among patients with coronary heart disease and high blood pressure who attended Shahid Rajaei Hospital. This was a quasi-experimental study with a pre-test, post-test, and a 3-month follow-up, including a control group. The study population included all individuals with a diagnosis of coronary heart disease and high blood pressure. The sample consisted of 30 patients selected through purposive sampling and randomly assigned to either the experimental or the control group. Data were collected using Ryff’s Psychological Well-being Scale (1989), Bond et al.’s Resilience Scale (2011), and Snyder et al.’s Life Hope Scale (1991). The ACT intervention was conducted over eight 90-minute sessions held weekly; however, the control group received no intervention. Data analysis was performed using a repeated measures analysis of variance (ANOVA) with SPSS-26. Findings indicated that Acceptance and Commitment Therapy significantly enhances psychological well-being, resilience, and hope for life in patients with coronary heart disease and high blood pressure (p < 0.05). In conclusion, ACT can improve psychological well-being, resilience, and life expectancy in patients with coronary heart disease and high blood pressure. Therefore, this approach can be used alongside medical interventions in healthcare centers.